Pharmacokinetics of trastuzumab deruxtecan (T-DXd), a novel anti-HER2 antibody-drug conjugate, in HER2-positive tumour-bearing mice. (2nd October 2020) - Okamoto, Hiromi; Oitate, Masataka; Hagihara, Katsunobu; Shiozawa, Hideyuki; Furuta, Yoshitake; Ogitani, Yusuke; Kuga, Hiroshi
Abstract: Trastuzumab deruxtecan (T-DXd, DS-8201a) is an antibody-drug conjugate (ADC), comprising an anti-HER2 antibody (Ab) at a drug-to-Ab ratio of 7–8 with the topoisomerase I inhibitor DXd. In this study, we investigated the pharmacokinetics (PK), biodistribution, catabolism, and excretion profiles of T-DXd in HER2-positive tumour-bearing mice. Following intravenous (iv) administration of T-DXd, the PK profiles of T-DXd and total Ab (the sum of conjugated and unconjugated Ab) were almost similar, indicating that the linker is stable during circulation. Biodistribution studies using radiolabelled T-DXd demonstrated tumour-specific distribution and long-term retention. DXd was the main catabolite released from T-DXd in tumours, with exposure levels at least five times higher than those in normal tissues and seven times higher than those achieved by non-targeted control ADC. Following iv administration of DXd, it was rapidly cleared from the circulation ( T 1/2 ; 1.35 h) and excreted mainly through faeces as its intact form. The PK profiles reveal that T-DXd effectively delivers the expected payload, DXd, to tumours, while minimising payload exposure to the systemic circulation and normal tissues. The released DXd is rapidly cleared from systemic circulation, presumably via the bile with negligible metabolism, and excreted through the faeces.